Curcumin: A Literature Review of Its Effects on Bone Health and Osteoporosis: - Tohidian, Mostafa; Moradi, Zahra; Jalalifar, Tofigh; Roshanisefat, Sarvenaz; Jamalnia, Sheida; Reihani, Elnaz (Galen Medical Journal, 2021)
Natural compounds can be used as a complementary or alternative medicine for many diseases, such as osteoporosis. Curcumin, a polyphenolic compound and the major active component of turmeric, is reported to play important roles in bone health and osteoporosis. By affecting proliferation, differentiation, lifespan, and activity of osteoblasts and osteoclasts, curcumin can directly modulate bone tissue hemostasis. Due to its insignificant side effects and several therapeutic properties, such as antioxidant, anticancer, antibacterial, antifungal, anti-inflammatory, and antirheumatic, it could be a potential therapeutic agent to prevent and treat osteoporosis. This review aimed to summarize the most important findings of in vitro, animal, and human studies in an effort to clarify the possible effects of curcumin on osteoporosis and to explain the exact molecular mechanism by which curcumin exerts its action. [GMJ.2021;10:e2129]